EXPLORE THE SYNERGISM OF SEDATIVE DOSE MEDETOMIDINE WITH TRAMADOL TO INDUCE ANALGESIC EFFECTS IN RABBITS - Mahmood. B. Mahmood (Basrah Journal of Veterinary Research)
The study was designed to evaluate the analgesic effects of Medetomidine and Tramadol in rabbits, to detect the best dose (as onset and duration) for antinociceptive in this model, also evaluate the antinociceptive effect as sedative doses in these drugs as a mixture by using electrical stimulator. Administration of Medetomidine alone at 200 µgkg B.W. (I.M) and Tramadol alone at 2 mg kg B.W. (I.P) were the best doses for relief pain induced by electrical stimuli. There was increased in the voltage change for pain ( 15, 30, 45, 60, 75, 90 minutes) in comparison with control and other doses for each drug. Administration of Medetomidine at 50 µg kg B.W. (I.M) with Tramadol at 0.5 mg kg B.W. I.P) significantly referred to synergism of the antinociceptive effect which induced analgesia in 100 % of the rabbits in comparison with other groups for each drug alone (at the same analgesic doses) without any overt side effects and without differences in glucose, glutathione, ALT and AST level in animals. The data of this study demonstrated the mixture of Medetomidine and Tramadol at low doses (subanalgesic doses) had a typical synergistic effect (super-additive) for inducing good and safe analgesia as well as its skeletal muscle relaxation in rabbits.